2018
DOI: 10.1002/dc.23992
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of Z‐stacking for teleconsultation between the USA and Colombia

Abstract: Introduction There is an emerging need for telecytology in Colombia as the demand for cytopathology has increased. However, due to economic and technological constraints telecytology services are limited. Our aim was to evaluate the diagnostic feasibility of using whole slide imaging with and without Z‐stacking for telecytology in Colombia, South America. Methods Archival glass slides from 17 fine needle aspiration smears were digitized employing whole slide imaging (WSI) (Nanozoomer 2.0 HT, Hamamatsu) in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Differently from surgical pathology, despite numerous international telepathology consultation services available, 13 very few studies on telecytology consultations using WSI have been published. [39][40][41][42] However, for second opinion consultation, WSI in cytology retains the same advantages, with studies showing a high degree of feasibility and confidence once the system is fully in action. 41 In addition, there is still the need of a close collaboration between institutions and an important investment strategy in the technical part.…”
Section: Area Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently from surgical pathology, despite numerous international telepathology consultation services available, 13 very few studies on telecytology consultations using WSI have been published. [39][40][41][42] However, for second opinion consultation, WSI in cytology retains the same advantages, with studies showing a high degree of feasibility and confidence once the system is fully in action. 41 In addition, there is still the need of a close collaboration between institutions and an important investment strategy in the technical part.…”
Section: Area Of Interestmentioning
confidence: 99%
“…[39][40][41][42] However, for second opinion consultation, WSI in cytology retains the same advantages, with studies showing a high degree of feasibility and confidence once the system is fully in action. 41 In addition, there is still the need of a close collaboration between institutions and an important investment strategy in the technical part. 40,42 WSI provides a high-quality file that can be showing how the training with WSI is effective to make students able to pass the proficiency tests.…”
Section: Area Of Interestmentioning
confidence: 99%
“…However, this makes the file image file size bulky. A recent paper by Mosquera-Zamudio et al [6] found an overall agreement of 58.8% to 88.2% between Colombian pathologists and the diagnosis given by a referral centre in United States by telecytology using whole slide imaging with Z stack technique. Most of the cytologists found the Z stacking to be diagnostically useful.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cytologists found the Z stacking to be diagnostically useful. Slower downloads and crashing of large files were some of the problems reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although conservative data retention policies or selective scanning can help institutions overcome these barriers, collecting images that require scanning at multiple focal planes (or z-stacking) still represents a technical challenge for many laboratories, despite potentially significant diagnostic gains. 5 Modern WSI scanners often support z-stack scanning, but the storage requirements are typically an order of magnitude greater than for single-plane scans. As laboratories begin to rely on their image management needs being met by networked servers or the cloud, this also introduces the issue of increased bandwidth requirements to support z-stacking for live WSI viewing.…”
Section: Introductionmentioning
confidence: 99%